Intramedullary Fibular Nail Fixation in an Elderly Patient with a Comminuted Weber C Ankle Fracture: A Case Report - Ajith Kumar Kannan; Anisha Tyagi; Johnny Dong; Elias Logothetis; Jay Bhuta; Rahul Mittal (Journal of Orthopaedic Case Reports)
Introduction: Ankle fractures are among the most common lower extremity injuries, accounting for approximately 9% of all fractures. Various methods exist for the internal fixation of fibular fractures, with open reduction and internal fixation using plates and screws currently regarded as the gold standard. However, plate and screw fixation is highly invasive and may lead to significant post-operative complications. Intramedullary (IM) nails, offering a less invasive alternative, have conventionally been indicated for non-comminuted Weber B and C fractures. To our knowledge, this is one of the few reports in the literature demonstrating the successful application of IM nails in a comminuted Weber C fracture. Case Report: We describe an 80-year-old female of Caucasian descent who presented with a comminuted Weber C ankle fracture following a fall. The patient was treated with fibular nail fixation, a minimally invasive technique that achieved successful alignment and stabilization. The patient had an uneventful recovery with no post-operative complications, highlighting the potential of this method in managing complex fractures in elderly patients with comorbidities. Conclusion: This case underscores the versatility and efficacy of IM nails in treating complex fibular fractures, including comminuted Weber C fractures. It highlights the clinical relevance of this technique as a less invasive and complication-reducing alternative to traditional plating systems, particularly for elderly patients with high surgical risks. The findings suggest that IM fixation has the potential to significantly advance fracture management strategies and reduce associated morbidity.